DEVELOPMENT OF RECIPES FOR FRUIT AND VEGETABLE MARINADES - ZUBKOVA, KATERYNA; STOIANOVA, OLНA; VALKO, MYKOLA; MAMAI, OLНA; TETYANA, YAKOVENKO (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article presents the results of research on the development of recipes for fruit and vegetable marinades. The authors have selected raw materials for the production of fruit and vegetable marinades. The paper investigates the use of garlic in the production of fruit and vegetable marinades and beetroot juice in the marinade. The chemical composition of the raw materials is analysed and their physiological effect on the human body is shown, which confirms the prospects of their use in the developed recipe of canned food.  A recipe for canned plums ‘Pickled plums with garlic’ was developed, combining naturalness and original flavour profile; the quality of the finished product was investigated according to the following indicators: organoleptic indicators, which determine the appearance, taste, smell and consistency; physicochemical indicators, including acidity, dry matter and other characteristics according to DSTU. The authors also developed a technological scheme of production, which includes all stages of preparation of raw materials and marinade. The technological scheme for preparing plums includes the following processes: washing, peeling, inspection, and blanching. Prepared plums are stuffed with garlic cloves, placed in jars and covered with marinade.  The marinade filling is a solution consisting of water, sugar, spices and acetic acid. Canned food is sealed and sterilised in autoclaves. The authors propose the use of beetroot juice in combination with spices for fruit and vegetable marinades, which ensures: enrichment of canned food with vitamins and minerals, improvement of organoleptic properties of the finished product. The introduction of a new type of fruit and vegetable marinades, such as ‘Plum marinated with garlic’, will create a competitive product that can take a worthy place both in the domestic and foreign markets.
Keywords: plum; garlic; fruit and vegetable marinade; recipe; bay